Real-time detection of wave profile changes - Chang, Shing I; Tavakkol, Behnam; Chou, Shih-Hsiung; Tsai, Tzong-Ru (My University, 2014)
A statistical process control (SPC) framework is proposed to detect potential changes of a wave profile on a real-time basis. In regular profile monitoring, change detection takes place when a complete profile is generated. In this study, the detection of a potential profile change takes place before the entire information on the profile of interest is fully available. The main research goal is to make a correct process decision as soon as possible. A real-world example of condensation-water-temperature profile monitoring was used to demonstrate the proposed framework. A simulation study was also conducted. The simulation results confirm that the proposed framework is capable of detecting profile changes without having to wait for the entire profile to be generated.
Keywords: Exponentially weighted moving average filter; Hotelling T² chart; Statistical process control; Profile analysis; Real-time monitoring